The Study Of Tourism Development Of Waterfront City (Case Study Of Ujong Blang Beach Of Lhokseumawe City) - Nasruddin; Nurlisa Ginting; Hilma Tamiami Fachruddin (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
Indonesia is an archipelagic country and has a long coastline. Beach tourism in Indonesia is very potential to be developed. Thus, it needs to be structured and developed in order to improve urban development. The tourism sector has important values and contributions with broad imensions, in economic, social-political, cultural, regional and environmental. The purpose of this research is to formulate the concept of Waterfront City in the development for the purpose of developing waterfront tourism. Analyzing the aspects needed for the construction of waterfront tourism in Lhokseumawe City. This paper raises the study of important aspects that need to be considered in the development of ourism areas, especially coastal tourism areas. The research was conducted with mixed methods, qualitative and quantitative. With this writing, it is expected to be an input to the tourism areas planning in Indonesia and in Lhokseumawe city in order to improve regional development, especially in the waterfront tourism sector. The conclusion with the existence of waterfront tourism planning, it is expected to have guidelines and important things related to regional development in order to increase economic growth